Corporate tax & Corporate Social Responsibility, A Smear Connection - Bui, Thanh Giang (2008)
The enhanced inspiration for Corporate Social Responsibility (CSR) strategy as a contemporary approach of doing business has triggered a new literature in corporate strategy and governance study. However, this desired strategy has drive business into image of good corporate citizens, a different direction in which taxation strategy is one of the efficient tools to maximise company and shareholder profits, regardless others related stakeholders. However, the channels through which businesses, especially global organisations view taxation and CSR strategy in speaking of corporate strategy in one piece, have not been well explained, both theoretically and empirically. Based on a solid theoretical framework, this paper uses a sample of FTSE 100 listed companies to explore new insights into the relationship between CSR and corporate tax strategy.